Keragaman Liana di Desa Uemea, Kecamatan Toili, Kabupaten Banggai, Sulawesi Tengah, Indonesia - Gina Latifa; Kurniasih Sukenti; Moh. Iqbal (JURNAL BIOS LOGOS, 2025)
Sulawesi is the largest island in the Wallacea region with about 53% of the area with about 500 endemic plant species including lianas. This study aims to inventory various types of lianas in Uemea Village, Toili District, Banggai Regency, Central Sulawesi, Indonesia. The method used in this research is the cruising method, which involves exploring the area around the research site. Found 25 species of lianas belonging to 14 families that have various types of climbing tools, which use stems, attached roots, tendrils, flagella, and petioles. The most common family found was Araceae with 9 species in Uemea Village, Toili District, Banggai Regency, Central Sulawesi, Indonesia.